2006
DOI: 10.1038/sj.ijo.0803328
|View full text |Cite
|
Sign up to set email alerts
|

Soft drink consumption and excess weight gain in Australian school students: results from the Nepean study

Abstract: We studied the relation between soft drink/cordial (a sweet, flavoured, concentrated syrup that is mixed with water to taste), fruit juice/drink and milk consumption in mid-childhood, and body mass index (BMI) status in early adolescence in a contemporary Australian cohort. In 1996/7, 268 children (136 males) were recruited from western Sydney at baseline (mean7s.d.: 7.770.6 years), and at follow-up 5 years later (13.070.2 years). Height and weight were measured at both time periods and overweight and obesity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
69
4
3

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 8 publications
5
69
4
3
Order By: Relevance
“…Likewise, in a group of non-Hispanic white girls that examined SSB intake at age 5 y, but not milk or fruit juice, predicted increases in % body fat, WC and prevalence of overweight from age 5 to 15 y (33). Similar findings were also demonstrated by Tam et al, in a small group of Australian children, where intake of soft drinks at 8 y, but not fruit juice or milk, was associated with subsequent 5 y excess weight gain (34).…”
Section: Discussionsupporting
confidence: 68%
“…Likewise, in a group of non-Hispanic white girls that examined SSB intake at age 5 y, but not milk or fruit juice, predicted increases in % body fat, WC and prevalence of overweight from age 5 to 15 y (33). Similar findings were also demonstrated by Tam et al, in a small group of Australian children, where intake of soft drinks at 8 y, but not fruit juice or milk, was associated with subsequent 5 y excess weight gain (34).…”
Section: Discussionsupporting
confidence: 68%
“…following the same group of people over time to see whether those with higher sweetened beverage intake gained more weight). Sixteen (59,61,62,64,(66)(67)(68)(70)(71)(72)(74)(75)(76)78,81,82) of the longitudinal studies reported a statistically significant positive association and eight reported no significant association between one or more categories of sweetened beverage intake and a measure of adiposity. Twelve of the sixteen longitudinal studies (59,62,64,(66)(67)(68)(70)(71)(72)75,76,81,82) that found a positive association received the highest quality 'plus' rating, compared to only three of the eight studies that did not detect a significant association.…”
Section: Secular Trends In Sweetened Beverage Consumptionmentioning
confidence: 99%
“…68 Reporting an observational study of 268 children born in western Sydney (the Nepean Study), Tam et al found increased sweet drink intakes did not displace milk consumption. 69 But noting the already low milk intake of Australian children in the 1995 ANN Study, 28 the increased sweet drink intake without milk displacement may actually reflect displacement of other fluids consumed, such as water.…”
Section: Consumption Of Sweet Drinks Juices and Milk By Childrenmentioning
confidence: 99%
“…99 A longitudinal study of 268 Australian children found no correlation between BMI and carbohydrate intake from fruit juice or milk, but soft drink or cordial intake at age 8 years was associated statistically with excess weight gain five years later. 69 A study of 1944 children aged 4-12 years in south-western Victoria found those regularly drinking sweet drinks, and those who had drunk more than two serves of juice, cordial or soft drink on the day prior to the survey day, were twice as likely to be overweight or obese. 100 Current research on associations between childhood obesity and caries suggests a relationship between obesity per se and increased caries prevalence.…”
Section: Sweet Drinks and General Health Of Childrenmentioning
confidence: 99%